Soluble TWEAK predicts hemodynamic impairment and functional capacity in patients with pulmonary arterial hypertension - Filusch, Arthur; Zelniker, Thomas; Baumgärtner, Christian; Eschricht, Sabine; Frey, Norbert; Katus, Hugo; Chorianopoulos, Emmanuel (Clinical research in cardiology, 2011)
Soluble TWEAK is a member of the TNF-alpha family of cytokines that has been shown to predict mortality in patients with heart failure. Pulmonary artery hypertension is a devastating disease, in which right ventricular function has been shown to be the major determinant of prognosis. In this hypothesis-generating study, we sought to evaluate the potential usefulness of sTWEAK in the prediction of disease severity in patients with pulmonary artery hypertension. We therefore conducted a retrospective analysis of sTWEAK serum levels in 95 stable patients with PAH. For all patients data on hemodynamic parameters, biomarkers and functional exercise tests were available. Compared to controls, patients with PAH showed significantly decreased levels of sTWEAK [median 314 pg/ml (interquartile range 217-473 pg/ml) vs. 405 (321-496 pg/ml); PAH vs. controls; P < 0.0001]. Soluble TWEAK levels were inversely correlated with NYHA class, pulmonary artery pressure, pulmonary vascular resistance, NT-proBNP, and troponin T levels and directly correlated with cardiac index, reduced 6-min walk test distances, and peak oxygen consumption. ROC curve analysis of sTWEAK levels in PAH patients revealed a cutoff value of 306 pg/ml for sTWEAK to be predictive of a reduced exercise capacity (6-min walk test <300 m) in patients with PAH with a similar predictive value compared to NT-proBNP. Intraindividual serial evaluation of sTWEAK revealed the potential of sTWEAK as follow-up marker in patients with PAH. In our hypothesis-generating study, sTWEAK was closely correlated to hemodynamic, functional, and serological indices of outcome in patients with PAH. Further prospective studies are needed to determine the role of sTWEAK as potential biomarker in patients with PAH.